Holding the Artist Accountable: Kay Boyle in the Modernist Press - Shannon LEVITZKE (E-REA)
“Holding the Artist Accountable: Kay Boyle in the Modernist Press” posits that there is a thematic consistency throughout Boyle’s publishing career, though it spanned roughly seven decades and included dozens of different little and mainstream magazines, that supersedes stylistic variations reflective of the periodicals in which she appeared. While her political aesthetic is less pronounced in her modernist magazine pieces than in her later writing in the popular press, overshadowed in part by her experiments with style, the work she published in these little magazines anticipates her later themes and shows her continuous interest in engaging with the outside world.